2012
DOI: 10.1136/bmj.e5823
|View full text |Cite
|
Sign up to set email alerts
|

Use of population based background rates of disease to assess vaccine safety in childhood and mass immunisation in Denmark: nationwide population based cohort study

Abstract: Objectives To predict the number of selected outcomes temporally associated but not caused by vaccination, to aid causality assessment of adverse events arising after mass immunisation in a paediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
14
3
1
Order By: Relevance
“…While in other studies this pattern has been reported even for younger age groups [31], our data did not show a clear picture for cases up to the age group of 20-29 years. This might be due to the very limited number of cases in the young population, where already single cases can have pronounced effects on age-specific estimates.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…While in other studies this pattern has been reported even for younger age groups [31], our data did not show a clear picture for cases up to the age group of 20-29 years. This might be due to the very limited number of cases in the young population, where already single cases can have pronounced effects on age-specific estimates.…”
Section: Discussioncontrasting
confidence: 55%
“…Studies from Denmark and Canada that had defined GBS cases by ICD codes only found crude [31] as well as age-standardized [32] IRs that were similar to ours; the Danish study was restricted to children up to the age of 17 [31] and showed crude IRs of 0.6 (95% CI 0.5-0.8) for the age group 4-9 years. Our study resulted in an IR of 0.7 (95% CI 0.4-1.2) in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…The searches identified a total of 5 843 potentially eligible studies, of which 49 satisfied our eligibility criteria and were therefore included in this review (see Figure ) . The key characteristics and main findings of all included studies are detailed in Table S1, and the quality assessment of these studies is summarized in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing CPRD incidence rates to those reported in the literature ( Table 4) the incidence rates we observed in the CPRD are between 10% and 88% lower than those observed in prospective follow-up studies [20,23,24] and electronic heath record studies in the Danish National Hospital Register [11,16] that all included A&E data. The exception is a third Danish study, which also used the Danish National Hospital Register (but only included primary discharge diagnoses) [25]. This illustrates the importance of understanding the methods used to produce the rates .The impact of A&E events is most evident in the VAESCO [16] data that used standardised methodology across several European electronic health record databases and shows a markedly higher incidence in the Danish data source that included A&E data.…”
Section: Discussionmentioning
confidence: 98%